2018
DOI: 10.1038/s41467-018-06368-x
|View full text |Cite|
|
Sign up to set email alerts
|

Gap junction protein Connexin-43 is a direct transcriptional regulator of N-cadherin in vivo

Abstract: Connexins are the primary components of gap junctions, providing direct links between cells under many physiological processes. Here, we demonstrate that in addition to this canonical role, Connexins act as transcriptional regulators. We show that Connexin 43 (Cx43) controls neural crest cell migration in vivo by directly regulating N-cadherin transcription. This activity requires interaction between Cx43 carboxy tail and the basic transcription factor-3, which drives the translocation of Cx43 tail to the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 70 publications
(109 reference statements)
7
133
1
1
Order By: Relevance
“…It is possible that Cx43 and Cx40 in the nuclei play distinct roles different from GJ function in these cells. Their C‐terminals might serve as a transcriptional factor, as was shown in amphibian and mammal models (Dang, Doble, & Kardami, ; Kotini et al, ). Notably, both Cx43 and Cx40 antibodies were against the C‐terminal and were localized to the nuclei.…”
Section: Resultsmentioning
confidence: 85%
“…It is possible that Cx43 and Cx40 in the nuclei play distinct roles different from GJ function in these cells. Their C‐terminals might serve as a transcriptional factor, as was shown in amphibian and mammal models (Dang, Doble, & Kardami, ; Kotini et al, ). Notably, both Cx43 and Cx40 antibodies were against the C‐terminal and were localized to the nuclei.…”
Section: Resultsmentioning
confidence: 85%
“…In fact, phosphorylation of Cx43 affects protein stability and GJIC activity 54,102,103 and we have detected changes in Cx43 phosphorylation pattern during hMSCs differentiation (chondrogenesis, osteogenesis and adipogenesis) but not under oleuropein treatment (in hMSCs and OACs) indicating that oleuropein affects Cx43 levels more than protein or gap junction plaque stability or regulation of the activity of these intercellular channels. Further, Cx43 channel-independent activities involve its signalling hub's ability to recruit proteins to the membrane 24,104-106 or its ability to control gene transcription by nuclear translocation and binding to RNA polymerase II and gene promoters 107 . We have recently reported that overactivity of Cx43 in OACs compromise the ability of these cells to redifferentiate by maintaining the stem-like 13 state enhanced by Twist-1 activity and tissue remodelling and proinflammatory agents such as IL-1ß 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 has channel-dependent and channel-independent functions (Kotini et al, 2018;Ribeiro-Rodrigues et al, 2017). CBX and Cx43DN act on connexin channel activity, suggesting a channel-dependent function in this context.…”
Section: Neutrophil Connexin-43 Is Required For Coordinated Calcium Fmentioning
confidence: 94%